MEMBANGUN BUDAYA LITERASI MEMBACA DENGAN MEMENFAATKAN POJOK BACA DI SDK MABHAMBAWA - Meo, Marsela Viktoria; Dhiu, Konstantinus Dua; Ngura, Elisabeth Tantiana; Efrida Ita (Global Action and Education for Society, 2025)
This research was conducted based on the low culture of reading literacy and several grade 2 students who still have difficulties in reading. One of the school literacy movement programs that can be carried out is to increase students' interest in reading through programs. reading corner. The aim of this research is to determine the role of reading corners on students' interest in reading. The type of research used in this research is descriptive qualitative, with research methods in the form of observation and literature study. The research subjects were students in class 2 of SDK MABHAMBAWA, the object of this research was the reading corner in clas 2 The research results show that reading corners play a very important role in growing and increasing students' interest in reading at school. Based on research, it can be concluded that with a reading corner, students can use the reading corner as the closest reading facility, as the closest reading material and also as a comfortable and interesting place to increase interest in reading.